Polystyrene Sulfonate-Chitosan Membrane from Styrofoam Waste as The Adsorbent for Fe (III) Metals from Ex-Tin Mining - Faizah Alivia Putri; Widia Widia; Addela Amelia; Robby Gus Mahardika (Jurnal Kimia Sains dan Aplikasi, 2023)
Styrofoam waste is difficult to degrade and decompose because it is included in inorganic waste, so it will negatively impact human health and the environment. A good and efficient method for chemical modifications that can convert Styrofoam into an appropriate material is needed. The heavy metal content in pond water is considered not good if used as drinking water because the heavy metal content in some ponds exceeds the quality standard for clean water, which is not good for health. Therefore, this research utilized Styrofoam waste in the environment with chemical modification into a sulfonated polystyrene-chitosan polyelectrolyte complex membrane as a heavy metal adsorbent in wastewater from a former tin mine. The PSS-chitosan membrane composition of 10:10 shows better adsorption capabilities than that of 12:8 and 8:12 on standard Fe metal. The adsorption efficiency of the PSS-chitosan membrane on Fe metal in underground water was (39.1 ± 3.1)%.